On nonlinear waves in elastic conductors under a magnetic field - Chakraborty, S. (Archives of Mechanics, 2002)
A study of the behavior of magneto-elastic waves in a nonlinear isotropic elastic conductor by applying the method of multiple scales and perturbation has been made for a general displacement wave, under the action of an arbitrarily directed, uniform magnetic field. While in the case of transverse magnetic field the shock the waves are formed, it has been shown here that, under an oblique magnetic field, the wave is distorted without the formation of shocks.